Bile is a reliable and valuable source to study cfDNA in biliary tract cancers - Li, Zhanghui; Liu, Yelei; Fu, Junhui; Mugaanyi, Joseph; Yan, Junrong; Lu, Caide; Huang, Jing (Frontiers in Oncology, 2022)
Objective The aim of this study is to determine the clinical efficacy of bile-derived liquid biopsy compared with plasma and tumor tissue biopsy in patients with biliary tract carcinoma (BTC). Methods A total of 13 patients with BTC were enrolled in this cohort. Tumor tissue, bile, and plasma samples were obtained and analyzed using next-generation sequencing for genomic profiling. Results Bile and plasma samples were collected from all 13 patients, and 11 patients also had matched tumor tissues available. The cell-free DNA (cfDNA) concentration was significantly higher in the bile supernatant than in plasma (median: 1918 vs. 63.1 ng/ml, p = 0.0017). The bile supernatant and pellet had a significantly higher mean mutation allele frequency (MF) than plasma (median: 3.84% vs. 4.22% vs. 0.16%; p < 0.001). Genomic alterations were predominantly missense. Both bile supernatant and pellet had significantly more genomic alterations than plasma (average: 9.3 vs. 7.2 vs. 2.3 alterations per sample; p < 0.01). Among the top 10 most frequent genomic alterations, the consistency between bile supernatant and tumor tissue was 90.00% (18/20), that between bile pellet and tumor tissue was 85.00% (17/20), and that between the plasma and tissue was only 35.00% (7/20). MAF of both bile supernatant and pellet was positively correlated with that in tissue samples (ρ < 0.0001, spearman r = 0.777, and ρ < 0.0001, spearman r = 0.787, respectively), but no significant correlation with tissue was found in the plasma (ρ = 0.966, spearman r = 0.008). Furthermore, additional genomic alterations could be detected in bile supernatant and pellet than in tissue. Potential targets for targeted therapy were identified in bile supernatant and pellet. Regarding copy number variation (CNV) and chromosomal instability (CIN) detection, four additional CNVs from two patients were detected in the bile supernatant that was not detected in tissues (i.e., amplification of TERC, IL7R, RICTOR, and TERT). CIN was significantly higher in tumor tissue than in plasma. The CIN of the bile was also significantly higher than that of plasma. There was no significant difference in CIN between the tissue and the bile supernatant. Conclusion The consistency of all genomic alterations and tumor tissue-determined genomic alteration in the bile supernatant/pellet was significantly higher than in plasma. Bile supernatants/pellets are better for genetic sequencing and may also have potential clinical value to guide targeted therapy and evaluate prognosis. Bile cfDNA may be a feasible substitute for tumor tissue in the genetic testing of patients with BTC.